Unique responses of Helicobacter pylori to exogenous hydrophobic compounds. (July 2020) - Shimomura, Hirofumi; Wanibuchi, Kiyofumi; Hosoda, Kouichi; Amgalanbaatar, Avarzed; Masui, Hisashi; Takahashi, Takashi; Hirai, Yoshikazu
Graphical abstract: Highlights: Lipids of Helicobacter pylori differ from those of typical Gram-negative bacteria. H. pylori characteristically interacts with various exogenous lipids. Myristate of H. pylori lipid contributes to the specific interaction between lipids. Abstract: Helicobacter pylori is a pathogen responsible for peptic ulcers and gastric cancers in human. One of the unique biological features of this bacterium is a membrane lipid composition significantly differed from that of typical Gram-negative bacteria. Due to its unique lipid composition, the responses of H. pylori to various exogenous lipophilic compounds significantly differ from the responses of typical Gram-negative bacteria to the same lipophilic compounds. For instance, some steroidal compounds are incorporated into the biomembranes of H. pylori through the intermediation of the myristoyl-phosphatidylethanolamine (PE). In addition, H. pylori shows high susceptibility to bacteriolytic action of lipids such as 3-carbonyl steroids, vitamin D, and indene compounds. These lipids are also considered to interact with myristoyl-PE of H. pylori membranes, and to ultimately confer the bactericidal action to this bacterium. In this study we summarize the lipids concerned with H. pylori and suggest the possibility of the development of chemotherapeutic medicines that act on the membrane lipid component of H. pylori .